Slovenske predelovalne dejavnosti in faktorska intenzivnost v proizvodnji - Černoša, Stanislav (Naše gospodarstvo, 2008)
This paper presents results of the measurement of horizontal and vertical intra-industry trade (IIT) for Slovenia''s manufacturing activities at the second and the third-digit level of the ISIC. Vertical IIT is separated on VERT1, which represents higher quality products, and on VERT2, which represents lower quality products. This separation shows that VERT1 comprises approximately one third and VERT2 comprises two thirds of vertical IIT. We present results of the analysis only for those manufacturing activities which show prevailing IIT specialisation in production of high quality products. The results also show that presented manufacturing activities mainly use labour intensity in production.
Keywords: mednarodna trgovina; mednarodna menjava; predelovalna industrija; proizvodi; industrijski izdelki; Slovenia; Slovenija